[Mari Katus 1]
Eger Basilika, castle, Zolika 3 years old, 2 children playing, grandparents, bath the baby, changing nappy, formal dinner, the whole family down the ground with toys, Zoo, parents pushing pram, newborn baby, on the cake: Öcsike 2 years old